Getting the Most out of Social Media: Strategic Practices When Using Social Media - Caroline R. Warwick; Lauri M. Baker; Jessica C. Fernandez; Joy Rumble (EDIS)
This EDIS publication is designed for Florida professionals, agriculturalists, organizations, and producers looking to develop a better understanding of social media platforms and get the most out of their social media usage. This publication specifically focuses on 15 practices for strategic social media use. Minor revision by Caroline R. Warwick, Lauri M. Baker, Jessica C. Fernandez, and Joy N. Rumble; published by the UF/IFAS Department of Agricultural Education and Communication; 3 pp.